2022
DOI: 10.1088/1742-6596/2168/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis between Meteorological Factors and Pollutants Based on Copula Theory

Abstract: In recent years, the continuous acceleration of industrial and agricultural production has aggravated the deterioration of the environment and seriously affected people’s health. Gas pollutant index has become an important indicator to measure air quality. Taking a region of China as the study subject, this paper firstly uses the monitoring data of air pollutants in 5 years and meteorological data (rainfall, temperature and wind speed) of meteorological observation stations in the same period. Then, the autoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…In addition to emission sources, weather conducive to the accumulation of pollution is another reason to consider. Adverse weather conditions are considered one of the main reasons for Southeast Asia and Thailand's severe air pollution in recent years, as can be seen from many researchers who studied meteorological factors during air pollution (Amnuaylojaroen et al, 2020;Bran et al, 2022;Chao & Min, 2021;Liu et al, 2020;Ma et al, 2022;Qi et al, 2021;Wang & Li, 2022). These researchers found that most air pollution and meteorological factors have prominent seasonal and regional characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to emission sources, weather conducive to the accumulation of pollution is another reason to consider. Adverse weather conditions are considered one of the main reasons for Southeast Asia and Thailand's severe air pollution in recent years, as can be seen from many researchers who studied meteorological factors during air pollution (Amnuaylojaroen et al, 2020;Bran et al, 2022;Chao & Min, 2021;Liu et al, 2020;Ma et al, 2022;Qi et al, 2021;Wang & Li, 2022). These researchers found that most air pollution and meteorological factors have prominent seasonal and regional characteristics.…”
Section: Introductionmentioning
confidence: 99%